Experience with surgical options for managing atonic post-partum haemorrhage - Saha, Rachana; Karki, Chanda; Padhye, Saraswati M (Nepal Journal of Obstetrics and Gynaecology, 2008)
Aim: To analyse the measures taken for controlling primary Post-partum haemorrhage (PPH). Methods: A hospital based descriptive and retrospective study was carried out from 1st January 2005 to 31st December 2006 in the department of Obstetrics & Gynaecology at KMCTH. All patients of having primary Post-partum haemorrhage were analysed for the treatment they received. Results: There were 15 cases of primary Post-Partum Haemorrhage (PPH) from a total delivery of 700 in the year 2005. 9 cases were solely of atonic post-partum haemorrhage. 2 cases were genital tract injuries, 1 case of retained placenta, 1 case of vulval haematoma and 2 cases were of combined cervical tear and atonic primary post-partum haemorrhage. Atonic post-partum haemorrhage remained most important cause. The most common treatment was use of oxytocic. Surgical procedure bilateral uterine artery ligation was frequently performed in 6 cases but it was not effective as a single procedure. B-Lynch brace suture was applied in 5 cases and was successful without further intervention. There were 2 maternal deaths from post-partum haemorrhage. In the year 2006 total number of deliveries was 835 and there were total 11 cases of post partum haemorrhage. The trend changed to from atonic PPH to traumatic PPH. There were 8 cases of traumatic PPH and there were 2 cases of placenta accrete. There was one case of atonic PPH. The overall incidence in two years was 1.6%. Conclusion: Among the various surgical methods adopted B-Lynch brace suture was found to be simple, effective and minimally invasive. Keywords: Atonic post-partum haemorrhage (PPH), surgical management of PPH.  doi:10.3126/njog.v3i1.1432 NJOG 2008 May-June; 3(1): 10 - 13